Ethics, Gesture and the Western - Michael Minden (Performance Philosophy, 2017)
This paper relates the Western Movie to Agamben’s implied gestural zone between intention and act. Film is important in the realisation of this zone because it was the first means of representation to capture the body in movement. The Western movie explores the space of ethical indistinction between the acts of individual fighters and the establishment of a rule of law, or putting this another way, between violence and justice. Two classic examples of an archetypal Western plot (Shane, 1953 and Unforgiven, 1991) that particularly embodies this are cited. In both a gunfighter who has forsworn violence at the start is led by the circumstances of the plot to take it up once more at the conclusion. In these terms all the gestures contained between these beginning- and end-points are analysable as an ethics of gesture because, captured as gestures, they occupy the human space between abstraction and action, suspended between them, and reducible to neither.  David Foster Wallace's definition of this narrative arc in Infinite Jest (and embodied in it) is adduced in order to suggest a parallel between Agamben's notion of an ethics of gesture, and an ethics of genre.